Rings [videorecording (DVD)] - Lutz, Matilda; Roe, Alex, 1990-; Galecki, Johnny; D'Onofrio, Vincent (Paramount Home Entertainment, 2017)
A young woman becomes worried about her boyfriend when he explores a dark subculture surrounding a mysterious videotape said to kill the watcher seven days after he has viewed it. She sacrifices herself to save her boyfriend and in doing so makes a horrifying discovery: there is a "movie within the movie" that no one has ever seen until now.